Atribuições dos agentes comunitários em saúde bucal : avaliação pela metodologia Delphi - Sass, Alex Luís (2015)
The objective of this research was to define responsibilities of Community Health Agents (CHAs) in the area of oral health through Delphi Methodology. This methodology used a logical theoretical model with initial questionnaire, which was sent to 30 participants. 10 managers working in the coordination of national oral health, state or municipal, 10 researchers or academics with post graduate degree in public health dentistry and 10 professional dentists working in the primary health care network in ESB (oral health team). The theoretical references were ministerial publications in the area of CHA and ESB. The logical theoretical model, followed by questionnaire was inserted in FORMSUS platform, which sent an access link with password for each participant by e-mail and participants remained anonymous. The participants answered the questionnaire evaluating their agreement with each question, on a scale from 0 to 10. There were thirty-four closed questions where consensus was measured when they reached an average of ≥ 7 and SD <3. Still, there were six open questions that allowed inclusion of comments and justifications. The analysis of these open questions by the team coordinating the research created new questions to be included in the second round of the questionnaire. A last round still tried to define a classification of the importance of each criterion by assigning the same weight to them as the median. The result was a final matrix with 36 criteria organized in six work dimensions. This study provides an objective image of the work of the Community Health Agent. The same demonstrates ACS 'ability to carry out promotion activities, surveillance, prevention and oral health education. This matrix can be used in order to define indicators CHA worker process in oral health